Ultraviolet radiation, but not γ radiation or etoposide-induced DNA damage, results in the phosphorylation of the murine p53 protein at serine-389 - Lu, Hua (The National Academy of Sciences, 1998)
Polyclonal antibodies were produced and purified that selectively react with a p53 epitope containing the murine phosphoserine-389 or the human phosphoserine-392 residue, but not the unphosphorylated epitope. These antibodies, termed alpha-392, were employed to demonstrate that the phosphorylation of this serine-389 residue in the p53 protein occurs in vivo in response to ultraviolet radiation of cells containing the p53 protein. After ultraviolet radiation of cells in culture, p53 levels increase and concomitantly serine-389 is phosphorylated in these cells. By contrast, the serine-389 phosphorylation of the p53 protein was not detected by these antibodies in the increased levels of p53 protein made in response to γ radiation or the treatment of cells with etoposide. These results demonstrate an ultraviolet responsive and specific phosphorylation site at serine-389 of the mouse or serine-392 of the human p53 protein. Previous studies have demonstrated that this phosphorylation of p53 activates the protein for specific DNA binding. This study demonstrates in vivo a unique phosphorylation site in the p53 protein that responds to a specific type of DNA damage.